1680 m. katekizmo glosarijus - Laučka, Alfonsas (Baltistica, 1968)
THE GLOSSARY OF THE CATECHISM OF 1680 The article presents an analysis of the Lithuanian-English glossary attached to the Catechism of 1680 – of only extant copy of which is preserved in the British Museum (PRADZIA PAMOKSLA, Printed Books Department, С 38 b 47, 1680). The glossary is an important cultural document testifying to the Lithuanian-English linguistic contacts of the 17th century. The manuscript glossary contains ca. 250 entries. Lithuanian words and phrases arranged in the alphabetical order are taken from the texts of the Catechism. The character of mistakes found in the glossary indicates that the compiler’s command of Lithuanian was poorer than that of English. Spelling peculiarities of English words are characteristic of English spelling of the late 17th and early 18th centuries. It has not yet been possible to identify the compiler and to determine the purpose of the glossary.